The Existence of Entrepreneurship Skills on Teachers and Prospective Teachers: A Survey - Siswanto Siswanto; Sukarno Sukarno; Sri Haryati (AL-ISHLAH: Jurnal Pendidikan, 2023)
Entrepreneurship skills are very important to be provided to prospective teachers and teachers through a learning scheme. Before designing a learning scheme, it is necessary to do a mapping to identify weaknesses and strengths in the achievement of entrepreneurship skills. This research was conducted to identify the achievement of entrepreneurship skills of prospective teachers and teachers. In addition, it also identifies the learning process carried out in order to train these entrepreneurial skills. The study was conducted using a survey method, with a total of 77 prospective teacher participants (spread over several universities in Central Java) and 119 teachers (teachers in several schools in Central Java). Questionnaires are used to investigate the achievement of entrepreneurial skills. An analysis of the lesson plan document was carried out to identify the learning process carried out in an effort to train entrepreneurship skills. The study results indicate that entrepreneurship skills still need to be improved, especially for teachers and prospective teacher students, especially the innovative aspect. In addition, this study succeeded in describing how learning activities were carried out to practice entrepreneurship skills.